Evaluation of a parent-delivered early language enrichment programme: Evidence from a Randomised Controlled Trial - Burgoyne, K; Gardner, R; Whiteley, H; Snowling, M; Hulme, C (Wiley, 2017)
Background It is widely believed that increasing parental involvement can improve children’s educational outcomes though we lack good evidence for such claims. The current study evaluated the effectiveness of a parent-delivered early language enrichment programme. Methods We conducted a randomized controlled trial (RCT) with 208 pre-school children and their parents living in socially diverse areas in the UK. Families were allocated to an oral language programme (N=103) or an active control programme targeting motor skills (N=105). Parents delivered the programmes to their child at home in daily 20-minute sessions over 30 weeks of teaching. Results Children receiving the language programme made significantly larger gains in language (d=.21) and narrative skills (d=.36) than children receiving the motor skills programme at immediate posttest. Effects on language were maintained 6 months later (d=.34), and at this point the language group also scored higher on tests of early literacy (d’s=.35 and .42). There was no evidence that the movement programme improved motor skills. Conclusions This study provides evidence for the effectiveness of a parent-delivered language enrichment programme. Further large-scale evaluations of the programme are needed to confirm and extend these findings.